All Days 2000
DOI: 10.2118/87302-ms
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Archie Equation in Carbonate Rocks

Abstract: Archie (1941) found an empirical equation for consolidate sandstone relating some formation parameters, porosity and water saturation. Archie equation is not easy to apply to rocks because formation parameters (a, m and n) are functions of electrical tortuosity. Electrical tortuosity is determined by pore geometry, tortuousity of the pore system and wettability which, affects oil - water distribution in the pores. Carbonate rocks with their complex pore systems and intermediate to oil wettabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Archie is only valid when the rock is water wet and free of clay with a uniform pore size distribution (Talabani et al 2000). Archie equation parameters (a, m, n) are functions of electrical tortuosity, which is related to the pore geometry and wettability (Talabani et al 2000).…”
Section: Petrophysical and Dynamic Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Archie is only valid when the rock is water wet and free of clay with a uniform pore size distribution (Talabani et al 2000). Archie equation parameters (a, m, n) are functions of electrical tortuosity, which is related to the pore geometry and wettability (Talabani et al 2000).…”
Section: Petrophysical and Dynamic Interpretationmentioning
confidence: 99%
“…Archie equation parameters (a, m, n) are functions of electrical tortuosity, which is related to the pore geometry and wettability (Talabani et al 2000). Carbonates are well known with their complex pore geometry and varying wetting characteristics, resulting in variations of the Archie exponents across the reservoir.…”
Section: Petrophysical and Dynamic Interpretationmentioning
confidence: 99%
“…Extensive laboratory studies has shown that Non-Archie behaviour could be attributed to multiple rock types, heterogeneous formations and anisotropic properties, multiniodal pore size, intragranular or micro-porosity, wettability, saturation history and hysteresis effect (drainage vs. imbibition) in the reservoir [3,4]. The main difficulty is to relate the electrical response from logging suites to the appropriate rock parameters and the in-situ dynamic mechanisms.…”
Section: Sw Determination: Concept and Challengesmentioning
confidence: 99%
“…Using three different techniques, conventional Archie's parameter techniques, core Archie's parameter estimation technique and a three-dimensional technique, the resulting profiles exhibited significantly differing water saturation values that were attributed to the uncertainty levels in the determination of Archie's parameters. Talabani et al [36] investigated the validity of Archie's equation for carbonate rock formations and concluded that the so called cementation factor m in Archie's equation is influenced by multiple factors, and may significantly differ for complex pore systems. Maute [37] outlined a data-analysis method for obtaining optimal Archie's parameter with reduced uncertainty for the general formation, outlining the challenges and variation in the parameters for a general rock reservoir formation.…”
Section: Introductionmentioning
confidence: 99%